Poznogotski krilni oltar v cerkvi sv. Križa v Kojskem (1515) in življenje v Brdih v 16. stoletju - Kolenc, Petra; Makuc, Neva (ZRC SAZU, Založba ZRC, 2016)
The scientific monograph (' Late Gothic winged altar of St. Cross of Kojsko (1515) and life in the Brda region of the 16th century') is dedicated to the 500 th anniversary of the unique late Gothic winged altar which dates back to 1515. The anniversary has offered numerous opportunities to illuminate the importance of this medieval cultural monument, which boasts not only Goriška Brda, but all Slovenia. Individual contributions in the book deal with the broader historical and social context of life in the Brda region of the 16th century.